2010
DOI: 10.1097/aln.0b013e3181f229b5
|View full text |Cite
|
Sign up to set email alerts
|

Brain Networks Maintain a Scale-free Organization across Consciousness, Anesthesia, and Recovery

Abstract: Background:Loss of consciousness is an essential feature of general anesthesia. Although alterations of neural networks during anesthesia have been identified in the spatial domain, there has been relatively little study of temporal organization. Methods: Ten healthy male volunteers were anesthetized with an induction dose of propofol on two separate occasions. The duration of network connections in the brain was analyzed by multichannel electroencephalography and the minimum spanning tree method. Entropy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 39 publications
6
71
0
Order By: Relevance
“…No differences in degree distribution were found between the three groups. Ciftçi (2011) noted a distinction between highly persistant and less consistent edges, somewhat in line with the results of Lee et al (Lee et al, 2010). Hierarchical clustering analysis of the MST showed that the connection between the hippocampus/parahippocampal gyrus on the one hand to the precuneus and posterior cingulate gyrus on the other hand, that is normally mediated by the angular gyrus and the inferior temporal gyrus, was disrupted in Alzheimer patients.…”
Section: Pioneering Worksupporting
confidence: 67%
See 3 more Smart Citations
“…No differences in degree distribution were found between the three groups. Ciftçi (2011) noted a distinction between highly persistant and less consistent edges, somewhat in line with the results of Lee et al (Lee et al, 2010). Hierarchical clustering analysis of the MST showed that the connection between the hippocampus/parahippocampal gyrus on the one hand to the precuneus and posterior cingulate gyrus on the other hand, that is normally mediated by the angular gyrus and the inferior temporal gyrus, was disrupted in Alzheimer patients.…”
Section: Pioneering Worksupporting
confidence: 67%
“…The distribution of connection survival times showed a power law, but did not change during the three different states, which was interpreted as reflecting adaptive reconfiguration of functional brain networks. Of particular interest, as can be seen in Fig.3 in (Lee et al, 2010), a subgroup of connections was much more stable over time. This subset could correspond to a stable backbone, and perhaps to the superhighways reported in theoretical work (Wu et al, 2006).…”
Section: Pioneering Workmentioning
confidence: 88%
See 2 more Smart Citations
“…A relative maintenance of global principles may reflect an adaptive reconfiguration of brain organization , a process that has also been suggested for propofol-induced transitions of consciousness in a recent EEG study (Lee et al, 2010). A significant increase in values of the clustering ratio ␥ was found during PI-LOC compared with wakefulness.…”
Section: Effects Of Pi-loc On Topology Of Brain Functional Graphsmentioning
confidence: 69%